Religiousness, Spirituality, and Psychological Distress in Taiwan - Liu, Eric Y. (Review of religious research, 2011)
Most of the previous research on religion and mental health has focused solely on Western, predominantly Christian societies. Using a 2004 national survey of 1,881 adults in Taiwan, this study investigates the relationships between multidimensional measures of religiousness/spirituality and psychological distress in an Eastern context. Our findings differ from previous studies in the West, showing that: (1) religious-based supernatural beliefs are associated with more distress; (2) daily prayer is associated with less distress; (3) engaging in secular-based supernatural activities like fortune-telling is related to more distress; and (4) the frequency of religious attendance is unrelated to levels of distress. Broader theoretical and empirical implications of these findings are discussed.